2019
DOI: 10.1038/s41598-019-52082-z
|View full text |Cite
|
Sign up to set email alerts
|

Trimethylamine-N-Oxide (TMAO) Predicts Cardiovascular Mortality in Peripheral Artery Disease

Abstract: Peripheral artery disease (PAD) is a major cause of acute and chronic illness, with extremely poor prognosis that remains underdiagnosed and undertreated. Trimethylamine-N-Oxide (TMAO), a gut derived metabolite, has been associated with atherosclerotic burden. We determined plasma levels of TMAO by mass spectrometry and evaluated their association with PAD severity and prognosis. 262 symptomatic PAD patients (mean age 70 years, 87% men) categorized in intermittent claudication (IC, n = 147) and critical limb i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
83
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 110 publications
(87 citation statements)
references
References 34 publications
3
83
0
1
Order By: Relevance
“…Furthermore, some meta-analyses have also confirmed a strong association between circulating TMAO levels and risk of fatal and non-fatal CVD events [92,93]. Patients with ischaemic stroke also exhibit higher TMAO levels than healthy controls [94], and increased TMAO levels also predict CVD mortality in patients with existing peripheral arterial disease [95]. Interestingly, so far only a very few reports exist investigating circulating TMAO levels in NAFLD cohorts.…”
Section: Trimethylamine N-oxide -Prototypic Microbiota-derived Metabomentioning
confidence: 93%
“…Furthermore, some meta-analyses have also confirmed a strong association between circulating TMAO levels and risk of fatal and non-fatal CVD events [92,93]. Patients with ischaemic stroke also exhibit higher TMAO levels than healthy controls [94], and increased TMAO levels also predict CVD mortality in patients with existing peripheral arterial disease [95]. Interestingly, so far only a very few reports exist investigating circulating TMAO levels in NAFLD cohorts.…”
Section: Trimethylamine N-oxide -Prototypic Microbiota-derived Metabomentioning
confidence: 93%
“…Furthermore, the role of carnitine in mediating TMAO synthesis has relevance to human health. Indeed, TMAO was suggested as one of the factors promoting atherosclerosis and increased cardiovascular risk (Koeth et al, 2013;Gao et al, 2017;Roncal et al, 2019). Later on, it has been shown that more than 200 variants exist in the coding region of TMAO producing enzyme, with different outcomes on the cardiovascular risk (Phillips and Shephard, 2020).…”
Section: Carnitine Trafficmentioning
confidence: 99%
“…However, in ApoE -/- mice transfected with human CETP, an increase in plasma TMAO was associated with a significantly reduced area of aortic lesions 19 . Nevertheless, recent clinical studies have shown a positive correlation between elevated plasma TMAO and an increased risk for major adverse cardiovascular events defined as death, myocardial infarction, or stroke 20 , 21 .…”
Section: Introductionmentioning
confidence: 99%